Determinants that influence the acceptance of generation Z in Malaysia towards complementary and alternative medicine - Tam, Weng Theng; Foo, Noreen (2023)
In recent years, the growing popularity of Complementary and Alternative Medicine (CAM) has become a noteworthy trend, even in the midst of remarkable advancements in Western medicine. This study examines the acceptance of CAM among Generation Z in Malaysia. Utilizing the Theory of Perceived Risk, quantitative research employing questionnaires is conducted among individuals aged 18 to 26, representing the Generation Z cohort. Employing judgmental sampling, a sample of 300 respondents is surveyed via a Google form. Microsoft Excel aids in data organization and analysis. Through Cronbach’s alpha, frequency distribution, and multiple regression analysis, the study concludes that effectiveness, mindset, and perceived affordability significantly impact acceptance, while side effects and treatment duration do not. This research enriches consumer behavior insights in healthcare, inviting further exploration of perceived risk's role in shaping consumer behavior. The exploration of this study not only contributed to the future researchers but also has practical impacts for government and CAM providers seeking to adapt healthcare services to meet the changing expectations and requirements of Generation Z.